Transparency and changing stakeholder roles in the digital age of sustainable agri-food supply chain networks - Otter, Verena; Robinson, Douglas M. (Frontiers in Sustainable Food Systems, 2024)
Society and policy demand greater sustainability of food systems, driving practitioners to improve the transparency of supply chain networks through digital innovation. Uncertainties regarding the structuring of relationships with primary and secondary stakeholders for sharing intangible data and information diminishes the potential for exploitation of digital transparency. While businesses are accustomed to organizing efficient flows of tangible goods, management research integrating digital transparency considerations to investigate and conceptualize structural changes in agri-food supply chain networks (AFSCNs) is scarce. This gap motivates the following four questions of this study: (1) Who are the primary and secondary stakeholders in the AFSCNs of the digital era? (2) What are their transparency interests? (3) How do AFSCN structures change with the emergence of digital innovations that can facilitate sustainability transition through greater transparency? (4) How to conceptualize those structural changes to AFSCNs? The netchain approach and respective transparency concept are integrated with classical stakeholder theory. Data was collected via a series of 21 semi-structured pilot interviews with technology providers in the EU agri-food sector and analyzed using structured content analysis. Results paint a complex picture of contemporary primary and secondary stakeholders of AFSCNs and their interests. Primary stakeholder interests lead to coopetition in vertical and horizontal relationships of the netchain and low transparency efforts by intermediaries. Both hamper the dissemination of digital innovations and the exploitation of their potential to improve AFSCN sustainability. Among secondary stakeholders, policymakers and governments, NGOs, and technology providers excel in being drivers of digital transparency for sustainability, with social media as a strong direct communication tool to reach netchain stakeholders, consumers, and research institutes/universities as collaborators and customers. The emergence of “information AFSCN” and “digital AFSCN” increases the complexity of the whole supply chain network through intermediation, reconfiguration, and emergence modes of change to underlying structures. Agri-food business managers, scientists, and policymakers should innovate in private and public governance to facilitate collaborative advantage and sustainability in a combination aligned with innovative digital transparency solutions.